Pengetahuan, Sikap Dan Tindakan Personal Hygiene Pedagang Makanan Jajanan Sekolah Dasar - Nurfadila, Nurfadila; Islam, Fahrul; Mappau, Zrimurti; Ashari, Agus Erwin (Jurnal Kesehatan Lingkungan Mapaccing, 2024)
Unsafe food is responsible for causing illness in approximately 1.6 million people per day worldwide, with around 40 percent of them being children. Food vendors have a significant potential to transmit diseases that can cause food poisoning. This study aims to assess the knowledge, attitudes, and practices related to personal hygiene among elementary school food vendors in Mamuju Sub-district, Mamuju Regency in 2023. The research method used in this study is descriptive research. The population in this study includes all food vendors at elementary schools in Mamuju Sub-district, totaling 30 vendors. The sample for this study is food handlers, using a total sampling method, with a total of 30 participants. The research variables are: knowledge, attitudes, and practices regarding the personal hygiene of food vendors at elementary schools. Data collection was conducted using a questionnaire based on the Regulation of the Minister of Health of the Republic of Indonesia Number 14 of 2021 concerning Standards of Business Activities and Products in the Implementation of Risk-Based Business Licensing in the Health Sector. Results: most respondents' knowledge falls into the good category, at 76.7%, most respondents' attitudes are also in the good category, at 96.7%, while most respondents' practices are in the poor category, at 70%. Conclusion: The majority of respondents have good knowledge and attitudes regarding personal hygiene, but these are not aligned with their practices, which are mostly in the poor category.